Constructing defect-rich Ni9S8/Fe5Ni4S8 heterostructure nanoparticles for efficient oxygen evolution reaction and overall water splitting. (21st April 2021) - Xu, Jinxiao; Ma, Yingjun; Wang, Jie; Guo, Xuyun; Su, Linghao; Ma, Chuanli; Gong, Liangyu; Zhu, Ye; Xuan, Cuijuan
Abstract: Designing electrocatalysts from the perspective of modulating electronic structure and morphology has received considerable research interest in enhancing the electrocatalytic performance for oxygen evolution reaction (OER). In this work, nickel–iron based sulfides were synthesized through a one-pot hydrothermal approach which is characterized as defect-rich Ni9 S8 /Fe5 Ni4 S8 heterostructured nanoparticles. The presence of two phases, numerous defects, and uniformly distributed nanoparticles with the porous structure are conducive to modulating electronic structure, facilitating electron and mass transport, allowing the effective accessibility of active sites. The as-prepared Ni9 S8 /Fe5 Ni4 S8 exhibits enhanced electrocatalytic OER activity and long-lasting stability, which needs an overpotential of 239 mV for yielding 10 mA cm −2 and long-term stability better than RuO2 . Furthermore, when employed in a two-electrode overall water splitting system, the catalyst coupled with Pt/C configuration exhibits comparable electrocatalytic performance to Pt/C and RuO2 based electrolyzer. This work not only offers a highly efficient and promising candidate catalyst for electrocatalytic water oxidation but also provides a simple synthesis method to heterostructured nanoparticles for other energy-related applications.